Global online interest in cervical cancer care in the time of COVID-19: An infodemiology study - Michelle Ann B. Eala; Ourlad Alzeus G. Tantengco (Elsevier, 2022)
Introduction: Internet search trends may gauge public awareness and interest in cancer and help identify key areas for improvement in public health interventions and awareness campaigns. During the COVID-19 pandemic, cervical cancer screening significantly decreased, and we hypothesized that this would be mirrored by a decreased online interest in cervical cancer care. Methods: Using the Google Trends database, we analyzed 2018-2021 global search trends in the following topics: cervical cancer, human papillomavirus, HPV vaccine, Cervarix, Gardasil, Pap test, HPV test, and colposcopy. Search trends were reported in the unit search volume index (SVI), which correlated with country-specific socioeconomic and epidemiologic characteristics. Results: We found a sharp decline in global online search interest in cervical cancer following the declaration of the COVID-19 pandemic, after which interest gradually increased. During the pandemic, SVI for "cervical cancer" and "Pap test" significantly decreased, while SVI for "HPV vaccine" significantly increased. Higher online search interest in cervical cancer care was found in low- and middle-income countries, and countries in Latin America and the Caribbean, Asia, and Europe, reflecting their burden of disease and recent developments in cervical cancer control. Conclusion: When the COVID-19 pandemic was declared, global online search interest in cervical cancer care decreased, reflective of the significant decline in cervical cancer screening rates during this time. Country-specific socioeconomic and epidemiologic characteristics correlated with online search interest in cervical cancer care. These global online search trends in cervical cancer may guide future public health interventions and awareness campaigns to eradicate this preventable disease worldwide.